Imkanur Rukyat Mabims 3-6,4 Criteria According to the Hisab Rukyat Team of Riau Islands Province’s Viewpoint - Angkat, M. Arbisora; Putra, Rizki Ananda (University of Muhammadiyah Sumatera Utara, 2024)
The purpose of this research is to determine the implementation of Imkanur Rukyat MABIMS 3-6.4 Criteria in Riau Islands Province and to find out the viewpoint of Hisab Rukyat Team of Riau Islands Province regarding this criteria. This research is qualitative research using Purposive Sampling Techniques to determine informants. In implementation, this criteria has not provided positive results because the documentation of rukyatul hilal activities carried out by the Hisab Rukyat Team of Riau Islands Province from 2022 to 2023 shows that the hilal has never been seen. The viewpoint of Hisab Rukyat Team of Riau Islands Province regarding this criteria are divided into 2 viewpoints. The first viewpoint is agree with this criteria because this new criteria was the rukyatul hilal result of hundreds years so that it can be scientifically justified. The second view viewpoint disagrees because this criteria still needs to be tested theoretically and practically. The dynamics and polemics as well as the Government's inconsistency in implementing this new criteria are also considerations in agreeing it.